2020
DOI: 10.1039/d0ra01825b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an external electric field on the rapid synthesis of MoO3 micro- and nanostructures by Joule heating of Mo wires

Abstract: The growth mechanism of layered α-MoO3 nano- and microplates on the surface of Mo wires during Joule heating has been investigated by application of an external electric field to the current carrying wire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A study of the effect of the simultaneous application of the two conditions, Joule heating and external electric field, has been carried out in the case of Mo wires. [56] A schematic of the experimental set up to apply the external field with copper electrodes perpendicular or parallel to the electric current responsible of the Joule heating is shown in Figure 8. The results show that the external field enhances the growth rate of α-MoO 3 nano-and microplates as compared with the growth of structures in absence of the electric field.…”
Section: Growth Of Oxide Nanowires and Other Structures During Joule Heating Of Metalsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study of the effect of the simultaneous application of the two conditions, Joule heating and external electric field, has been carried out in the case of Mo wires. [56] A schematic of the experimental set up to apply the external field with copper electrodes perpendicular or parallel to the electric current responsible of the Joule heating is shown in Figure 8. The results show that the external field enhances the growth rate of α-MoO 3 nano-and microplates as compared with the growth of structures in absence of the electric field.…”
Section: Growth Of Oxide Nanowires and Other Structures During Joule Heating Of Metalsmentioning
confidence: 99%
“…The results show that the external field enhances the growth rate of α-MoO 3 nano-and microplates as compared with the growth of structures in absence of the electric field. It was proposed [56] that the rapid growth is due to a thermally assisted electric mechanism which favor the cations diffusion toward the surface. Other effect of the application of electric field is the growth of nanostructures, dendritic arrangements, nanoplates, and clusters of nanocrystals (Figure 9) on the copper electrodes placed parallel to the Mo wire, as in Figure 8a, or in the arrangement plate-pointed electrodes shown in Figure 8b.…”
Section: Growth Of Oxide Nanowires and Other Structures During Joule Heating Of Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strip out these reports, here, we tried a new strategy to reduce N 2 O with silanes via metal-free catalyst. It is known that oriented external electric field (OEEF) had been proved an effective, green, and controllable catalytic method, not only for the structures and properties of molecules, but also for the catalysis of chemical reactions [40][41][42][43][44][45][46][47][48]. In 2004, Shaik et al first reported that the OEEF could control the selectivity of iron-oxo porphyrin with propene [49].…”
mentioning
confidence: 99%